KADAR AIR, pH DAN TOTAL MIKROBA DAGING AYAM YANG DITAMBAHKAN KUNYIT PUTIH (Curcuma mangga Val.) - Wala, John; Ransaleleh, Tiltje; Wahyuni, Indyah; Rotinsulu, Merri (ZOOTEC, 2016)
THE EFFECT OF WHITE TURMERIC (Curcuma mangga Val.) ADDITION ON CHICKEN MEAT AGAINST WATER CONTENT, pH AND MICROORGANISM NUMBERS. The purpose of this research was to determine the effect of the addition of white turmeric (Curcuma manggaVal.) on chicken meat at cold storage (4oC). This research used Split Plot Design with 2 treatment factors based on completely randomized design. The Main Plot contains of 4 treatments (A0 = without storage, A1 = 3 days storage, A2 = 6 days storage, A3 = 9 days storage) and the Sub Plot contains of 4 treatments (B0 = without white turmeric, B1 = 4% grating of white turmeric, B2 = 8% grating of white turmeric, B3 = 12% grating of white turmeric). The variable that observed are water content, pH and microorganism number. The result showed that the addition of white turmeric was not significant affected (P > 0.05) against water contentof chicken meat, however it was highly significant affected (P < 0.01) against pH and microorganism numbers of chicken meat. Storage time was highly significant affected (P <0.01) against water content, pH and microorganism numbers of chicken meat. The interaction between both of treatment factors was given highly significant affected (P < 0.01) against water content, pH and microorganism numbers of chicken meat. As a conclusion, the addition of white turmeric on chicken meat was not affected against water content, however it can decrease pH and obstruct microorganism activity. Keywords : chicken meat, white turmeric, pH, water content, microorganism numbers